STRATEGI PEMBELAJARAN ACTIVE LEARNING DALAM MENINGKATKAN KEMEMPUAN MEMBACA AL QUR'AN PADA ANAK USIA DINI - Ifan Ali Alfatani; Zaenol Fajri; Uun Ayu Faradini (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Early childhood development and growth occur from birth to age six, an expeditious period in a child's development. Reading from the Qur'an is one of many learning activities that should be harmonized with a child's growth and development process to provide guidance and direction. It is our duty as educators to assist in teaching children about religion. The teacher's capacity to select strategies appropriate for early childhood is required to facilitate the teaching of learning to students. Since early childhood is characterized by being active, active learning is a suitable learning strategy. This study aimed to ascertain whether active learning increased children's capacity to read the Qur'an. This kind of study is called classroom action research, and it consists of three stages: preparation, implementation, and observation, as well as reflection. In this study, observation and interviews were the primary data collection methods. The outcomes of this class action study from cycles one to three can be excellent and efficient. Active learning is being used to implement research at a steadily increasing rate throughout each process. Enhancing early childhood's capacity for meeting expectations and developing exceptionally well in the first cycle improved to 67.78% in cycle 2, 77.78% in cycle 2, and 86.67% in cycle 3. Therefore, active learning can enhance young children's capacity to read the Qur'an at Tahfidz Al Fatih Bondowoso Kindergarten.